Travellers with prosthetic limbs, a neglected population. A perspective on what travel health practitioners need to know - Irmgard L. Bauer; Vikranth H. Nagaraja (Tropical Diseases, Travel Medicine and Vaccines, 2024)
Abstract Background The benefits of travel for the wellbeing of people of all ages and abilities are well known, though travellers with prostheses have so far been excluded. Limb loss, due to trauma, vascular disease, cancer, or infections requires a prosthesis for cosmesis and functionality. The life-changing event of losing a limb and the considerable psychological adjustment to accept an altered body image influence rehabilitation and self-management as well as the participation in social activities, such as sport and travel. The challenge of travel lies not only in transferring practical impediments encountered at home to another location; familiar coping strategies may require unexpected adjustments. After presenting background information on limb loss and prostheses, the purpose of this paper was to review literature on health advice for travellers with prosthetic limbs. Method All major data bases were searched for peer-reviewed literature using a variation of keyword combinations around travel and prosthetics. Relevant journals were searched individually, and selected authors and university departments contacted. No evidence-based results were obtained. The search then moved to grey literature including documents from relevant organisations, professional bodies, government websites, manufacturers, airlines, prosthetic/physiotherapy clinics, sport organisations to approaching amputees, including veterans and athletes, directly. Result The list of collated travel advice for people with artificial limbs relates to (1) trip preparation, (2) packing (especially considering the mechanical and/or electrical requirements of the prosthesis), (3) travelling by plane as the most covered mode of travel, and (4) navigating airports and airport security, which may be used by travel health practitioners while awaiting evidence-based guidelines. Conclusion This is the first paper on travel with a prosthetic limb in any field, including travel medicine. Therefore, travel health practitioners have no evidence-based ...